Void fraction measurement in cryogenic flows. Part II: Void fraction capacitive sensor performances in chilldown experiments. (December 2018) - Sakamoto, Yuki; Peveroni, Laura; Kobayashi, Hiroaki; Sato, Tetsuya; Steelant, Johan; Buchlin, Jean-Marie
Highlights: This work is the follow-up of Part I on a capacitance-based void fraction sensor. The EFA, widely applied in LN2 conditions, estimated the sensor accuracy to ± 6%. The void fraction deviation experimentally found was compensated to less than 2%. High-speed background light imaging was used as support metrology. The void fraction is correlated to the movies light intensity in a specific regime. Abstract: This manuscript describes the work performed on void fraction measurements a cryogenic flow by means of a customized capacitive sensor. In a preceding activity, described in Part I, the instrument was developed and validated at room conditions. In the current study, the probe is exploited to detect the gaseous content during liquid nitrogen chilldown experiments. The sensor performances are evaluated both numerically and experimentally. The numerical simulations lead to the development of a new calibration formula improving the sensor measurement accuracy down to ± 6.0%FS, within 99% confident interval. The experimental campaign mainly reveals a dependency of the sensor performance on the pressure and temperature variations during the cooldown of the test section. The so-called "thermal effect" therefore modeled and two compensation equations are derived. The void fraction results accordingly corrected, match the single-phase flows reference conditions within ± 2% discrepancy. Background light visualizations are also performed allowing the optical verification of the flow regimes. For a specific flow condition, a correlation between the recorded light intensity and the capacitive measurements is obtained. By means of the high-speed movies, the capacitive sensor response time is also evaluated to be 100 Hz.